Understanding the production and reduction of barium sulfate crystals through the use of additives and a controlled stirring rate - N. Karaman; R. S. Maulida; N. Fariana; A. P. Bayuseno; Lilik Suprianti (Jurnal Indonesia Sosial Teknologi, 2024)
Barium sulfate crystals are minerals responsible for scaling in piping systems. Controlling the growth of these crystals can use additives (FeCl2 and SrCl2) and varying agitation speeds. The research was to optimize the impact of additives and agitation speed on the results of crystal form using RSM through Minitab 19 with Box-Behnken Design. The optimum conditions using additive FeCl2 at a concentration of 25 ppm, a stirring speed of 120 rpm for 30 minutes, and a coefficient of determination (R2) of 90.995 provided 0.4485 gr of barium sulfate crystals. The optimum conditions, however, used SrCl2 additives at a concentration of 20.2049 ppm and a stirring speed of 459.394 rpm for 30 minutes, yielding 0.4345 g of barium sulfates with a coefficient of determination (R2) of 91.41%. The results of crystallizing barium sulfate without additives appear to be superior to those obtained with additives in terms of production. In contrast, additives of FeCl2 and SrCl2 can inhibit barium sulfate formation, resulting in a reduction in crystal mass